2017
DOI: 10.1007/s00484-017-1461-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal flowering patterns in Mediterranean Poaceae. A community study in SW Spain

Abstract: This study focused on phenological timing and spatial patterns in 30 Poaceae species flowering in spring in different types of plant cover (scrub, riverbank and pasture). Grass community composition was studied, and the influence of species and plant cover on the start date and duration of flowering was assessed from March to June in both 2014 and 2015. Twenty-nine sampling sites were selected for phenological monitoring using the BBCH scale. Data were subjected to GLMM analyses. Binary discriminant analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This can cause a dampening effect on the signal from local vegetation for the season as a whole. However, vegetation over a regional area is likely to contain a wide range of grass species dispersing pollen at various intervals, due to different flowering times (Cebrino et al, 2018), localized micro-climatic factors (Jackson, 1966) and varying management regimes (Theuerkauf et al, 2015). This efficient mowing could explain the effect of meso-gamma grass source areas (2 -10 km) and the absence of effects from micro-scale source areas for Lakeside.…”
Section: Transportation Distance and Meteorologymentioning
confidence: 99%
“…This can cause a dampening effect on the signal from local vegetation for the season as a whole. However, vegetation over a regional area is likely to contain a wide range of grass species dispersing pollen at various intervals, due to different flowering times (Cebrino et al, 2018), localized micro-climatic factors (Jackson, 1966) and varying management regimes (Theuerkauf et al, 2015). This efficient mowing could explain the effect of meso-gamma grass source areas (2 -10 km) and the absence of effects from micro-scale source areas for Lakeside.…”
Section: Transportation Distance and Meteorologymentioning
confidence: 99%
“…glomerata is by far the most common sub-species, defining the standard of the species (Mizianty 1990). Cebrino et al (2018) found that D. glomerata starts flowering around the same time in Spain, regardless of habitat. This holds true between years and locations (Cebrino et al 2016).…”
Section: Introductionmentioning
confidence: 99%